Developing tuberculosis drug information system using a throwaway prototype: Udayana Hospital case study - Rini Noviyani; Luh Arida Ayu Rahning Putri; I Nyoman Gede Budiana; Luh Gede Astuti; I Made Oka Widyantara; Ida Ayu Alit Widhiartini; Ida Bagus Nyoman Maharjana; Sagung Chandra Yowani; I Gusti Ngurah Anom Cahyadi Putra (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
Tuberculosis (TB) remains a major health problem in Indonesia, and efficient drug management is essential to ensure continuous treatment and prevent resistance. At Udayana University Hospital, manual recording and reporting often caused delays and errors, while integration with the National Tuberculosis Information System (SITB) was limited. This study developed a TB drug information system using the throwaway prototype model to address these challenges and enhance hospital workflow efficiency. The system implementation demonstrated measurable improvements in operational performance, with data entry errors reduced by 83% and the average recording time per patient shortened by 35% compared to the previous manual process. User feedback confirmed improved usability, accuracy, and reliability in supporting hospital workflows and timely reporting. In conclusion, the proposed system effectively improved the accuracy and efficiency of TB drug management while addressing hospital level operational challenges. This study demonstrates the applicability of the throwaway prototype model in healthcare information-system development and provides insights for scaling and integration with national TB programs.